2005
DOI: 10.1212/01.wnl.0000176036.07558.82
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy—An evidence-based review [RETIRED]

Abstract: Abstract-Objective:To assess the efficacy of carotid endarterectomy for stroke prevention in asymptomatic and symptomatic patients with internal carotid artery stenosis. Additional clinical scenarios, such as use of endarterectomy combined with cardiac surgery, are also reviewed. Methods: The authors selected nine important clinical questions. A systematic search was performed for articles from 1990 (the year of the last statement) until 2001. Additional articles from 2002 through 2004 were included using pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
149
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(157 citation statements)
references
References 37 publications
1
149
0
7
Order By: Relevance
“…5) In addition, neurosurgeons and/or patients' families often report postoperative subjective improvements or impairments in cognition for patients undergoing CEA. In fact, numerous studies have investigated objective changes in cognitive function following CEA using neuropsychological testing: just over half of these studies reported an improvement in cognition after CEA, but the remainder found no change.…”
Section: Introductionmentioning
confidence: 99%
“…5) In addition, neurosurgeons and/or patients' families often report postoperative subjective improvements or impairments in cognition for patients undergoing CEA. In fact, numerous studies have investigated objective changes in cognitive function following CEA using neuropsychological testing: just over half of these studies reported an improvement in cognition after CEA, but the remainder found no change.…”
Section: Introductionmentioning
confidence: 99%
“…13 It is estimated that carotid artery disease is responsible for 15% to 20% of all strokes. 14 The standard therapy for carotid artery revascularization is carotid endarterectomy (CEA), which is being compared with percutaneous carotid artery stent (CAS) placement in several patient subsets. Writing Group 5 focused on 3 current controversies:…”
Section: Writing Group 5: Controversies In Carotid Artery Revascularimentioning
confidence: 99%
“…Carotid stenosis accounts for 15–20% of all ischemic strokes [1]. Stroke recurrence in patients with symptomatic carotid stenosis can be prevented by carotid endarterectomy (CEA) with an absolute risk reduction of up to 17% [1].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke recurrence in patients with symptomatic carotid stenosis can be prevented by carotid endarterectomy (CEA) with an absolute risk reduction of up to 17% [1]. Although there is irrefutable evidence that CEA is beneficial in patients with >70% symptomatic stenosis, identifying other patients who may benefit from CEA continues to be a significant challenge.…”
Section: Introductionmentioning
confidence: 99%